Analisis Penggunaan Media Sosial Instagram Dalam Meningkatkan Kesadaran Dan Partisipasi Pengguna Terhadap Layanan LRT (Light Rail Transit) Sumatera Selatan - Suhendra, Suhendra; Laraskana, Tiara Nesva (Jurnal Publisitas, 2024)
This study aims to analyze the use of Instagram social media in increasing user awareness and participation of the SUMSEL LRT (Light Rail Transit South Sumatra) service. Instagram has become an important tool in building brand awareness and interacting with audiences. In the transportation industry, LRT SUMSEL also utilizes Instagram as a communication and promotion tool. However, there has not been much in-depth research on the effect of using social media on user awareness and participation of South Sumatra LRT services. This study used qualitative and quantitative approaches to collect data from LRT SUMSEL's official Instagram account and through an online survey to LRT SUMSEL's followers on Instagram. Data analysis involves content analysis, user responses, and interviews with selected users. The results of this study are expected to provide insight into the influence of Instagram social media usage strategies on user awareness and participation in South Sumatra LRT services. With a better understanding of the role of social media in the transportation industry, it is expected to increase the use of South Sumatra LRT services and the quality of public transportation in South Sumatera